Biochemical Markers of Iron Status Among Iraqi Patients at Different Severity Levels of Celiac Disease - Hasan, Hathama Razooki; Abudal Kadhum, Zahraa I.; Ghadhban, Jasim M. (Iraqi Journal of Science, 2024)
In people with a hereditary predisposition, gluten consumption causes celiac disease, a multifactorial autoimmune condition. The ensuing small intestine inflammatory process develops specific antibodies and causes various gastrointestinal and extra-intestinal symptoms with varying degrees of severity. Evaluation of the blood iron profile at various histological celiac disease severity in Iraqi patients was the goal of the current study. Seventy-five Iraqi patients with celiac disease, with a mean age of 18.68± 11.13 years, were the study's participants. These people tested positive for celiac antibodies and experienced gastrointestinal symptoms. Based on the disease histological severity, they were divided into two groups: marsh (III a, b, c) group and marsh (0, I) group. For comparison purposes, 46 people who appeared to be in good health and matched in age and gender to the patients utilized in the study were also included. The levels of iron, transferrin, hemoglobin, ferritin, total iron binding capacity, unsaturated iron binding capacity, and the percentage of transferrin that is saturated with iron were all measured. In comparison to the other patient groups under study, celiac patients (marsh III) group, and particularly those of group (marsh III c), showed a substantial drop (p<0.05) in iron, the percentage of transferrin saturating with iron, the levels of each ferritin and of hemoglobin. The total iron binding capacity and the unsaturated iron binding capacity showed a significant elevation (p<0.05) in (marsh III c) patients’ group, meanwhile non-significant differences (p> 0.05) were found in transferrin concentration. Moreover, significant differences (p< 0.05) were obtained in the iron profile between celiac patients who followed strict gluten free diet and those patients with gluten contained diet.